Determinants of community participation in ecotourism programs in Bali, Indonesia - Utama, I Gusti Bagus Rai; Junaedi, I Wayan Ruspendi; Krismawintari, Ni Putu Dyah (Institute of Advanced Engineering and Science, 2024)
In the case of Indonesia, most of the tourist attractions offered and advertised are protected forests. This research seeks to find a balance between these two interests, so the purpose of this research is actually to determine the determinants of local community involvement in ecotourism development in Bali. This research uses quantitative methods described in the form of descriptive, and factor analysis according to the results of the survey with informants in the ecotourism of West Bali National Park, Buyan Tamblingan, Bali Mangrove, Batur Kintamani, and Lembongan. Eight factors determine community participation in ecotourism programs in Bali, namely: i) the role of leaders and business opportunities, ii) the factor of mindset and industry cooperation, iii) the factor of income, socialization, and commitment, iv) the factor of awareness of nature conservation, v) the factor of optimism to get money and knowledge, vi) the factor of facilities and independence, vii) the factor of training, interest, and participation, and viii) the factor of skills and funding.